2003
DOI: 10.1177/0148607103027006389
|View full text |Cite
|
Sign up to set email alerts
|

Improving nutritional screening of hospitalized patients: the role of prealbumin

Abstract: Use of screening questionnaires may miss or delay identification of malnourished patients. PAB screening/assessment may improve identification of those patients requiring nutrition intervention and thus enhance the care of hospitalized individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
63
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(65 citation statements)
references
References 0 publications
1
63
0
1
Order By: Relevance
“…However, its function in nutritional screening and in predicting mortality is controversial (Ferguson et al, 1993;Brugler et al, 2002;Langkamp-Henken et al, 2005;Devoto et al, 2006;Carriere et al, 2008). Robinson et al (2003) found prealbumin to be a significant predictor of malnutrition, whereas serum albumin and retinol-binding protein were not. Retinol-binding protein behaves similarly to prealbumin, but has an even shorter half-life (6-12 h).…”
Section: Discussionmentioning
confidence: 99%
“…However, its function in nutritional screening and in predicting mortality is controversial (Ferguson et al, 1993;Brugler et al, 2002;Langkamp-Henken et al, 2005;Devoto et al, 2006;Carriere et al, 2008). Robinson et al (2003) found prealbumin to be a significant predictor of malnutrition, whereas serum albumin and retinol-binding protein were not. Retinol-binding protein behaves similarly to prealbumin, but has an even shorter half-life (6-12 h).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the independent relationship between outcomes and also the single components of NRS-2002 have been recently associated with outcome [5]. This does not mean that the choice of analytical criteria should be preferred to that of simple and widely applicable validated tools, because the latter (albumin, prealbumin, weight loss and reduced food intake) can account for the effect of disease on nutritional risk only in part [30][31][32][33]. Our choice was not random and reflects all the efforts that should be made to identify, and so to treat, every patient at risk.…”
Section: Discussionmentioning
confidence: 99%
“…This type of classification, however, may often reflect severity of illness and the magnitude of the SIRS rather than nutritional status. When screening protocols that use prealbumin have been compared with a 2-stage process involving a screening questionnaire followed by an assessment by a professional dietitian, the prealbumin protocols identified many more patients considered to be malnourished (7,8 ). The authors have tended to interpret this finding as showing the increased sensitivity of prealbumin in detecting malnutrition, rather than the lack of specificity of this test.…”
mentioning
confidence: 99%